Isolation, Identification and Antioxidative Activity Of Phenolics in Palm Oil Mill Effluent - Halimoon, Normala (2006)
The objectives of the study are to isolate, and identifl the phenolic compounds present in the palm oil mill effluent (POME) and evaluate their antioxidative activity. Combinations of column and partition chromatography were used in the isolation of the phenolic compounds. Antioxidative activities of the POME hctions were evaluated for fke radical scavenging activity, lipid thiocyanate, &carotene-linoleate and reducing assays. Identification of the phenolic compounds in POME filtrate was carried out using high performance liquid chromatography (HPLC), followed by confirmation of the compounds using gas chromatography mass spectrometry (GCIMS) and liquid chromatography mass spectrometry (LCIMS). The study revealed the presence of cinnamic acid derivatives, which were measured at 320 nm. These included chlorogenic, p-cournaric, caffeic, ferulic acids and rutin hydrate. Benzoic acid derivatives, which were identified as protocatechuic, gentisic, p-hydroxybenzoic and vanillic acids were also present when measured at 260 nrn. Hydrolysis of the sample did not affect the chromatographic pattern obtained indicating the stability of the phenolic compounds in the POME filtrate. Flavan-3-01 groups (catechins) were identified from ytterbium precipitation method. Four fractions have been isolated from POME filtrate based on flash chromatography coupled with uv/vis detection. The antioxidative activity of each h t i o n was then evaluated. All the POME fractions demonstrated excellent antioxidative activity in all the assays used. This is especially true for both Fractions 3 and 4. Fraction 1 exhibited highest antioxidative activity based on reducing assay followed by Fraction 3 indicating the excellent metal chelating ability of the phenolics in these hctions. The POME fractions were found to contain different levels of total phenolics, which did not necessarily correspond to the strength of antioxidative activity, measured for each hction. Fraction 3 showed strong free radical scavenger and phenolic content was also high. Fraction 2 showed low antioxidant activity, while total phenolic content was low. However, Fraction 4 showed high antioxidant activity with low total phenolic content. This indicates the presence of different phenolic compounds in the different hctions. Results showed that Fraction 1 contained an unknown polar compound and protocatechuic acid with strong metal chelating activity, Fraction 2 was rich in phydroxybenzoic acid, Fraction 3 contained three unknown cinnamic acid derivatives and Fraction 4 contained known cinnamic acid derivatives compounds including p-coumaric acid, rutin hydrate and ferulic acid with lower polarity. The cinnamics in Fraction 3 consistently exhibited higher antioxidative properties compared with benzoics in Fraction 2. Combination study of the fractions revealed that mixture of Fraction 3 and ascorbic acid had better hx radical scavenging activity. However, the synergistic effect was observed only at low concentration of 2.5 and 5 mgll of Fraction 3 and ascorbic acid. The individual compounds of Fraction 3 (cimamic acid derivatives) including Compounds 14, 15 and 16 exhibited the highest ike radical scavenging activity. Highest antioxidative activity was also measured when Compounds 15 and 16 were combined (double combined) while for triple combinations, the highest activity was seen with Compounds 13, 14, and 15 at 15 mgA of total phenolic contents. The results showed that there was a synergistic effect between the compounds in particular those in Fraction 3. GCMS and LC/MS were employed to confirm identifj of unknown compounds in Fraction 3. Three compounds in Fraction 3 were observed to exhibit similar absorbance spectra using HPLC with diode array detection. LC/MS revealed presence of dimer with maximum molecular weight of 335 dz. GCMS revealed the presence of compounds with a general cinnamic acid structure and derivatives with silylate group. Antioxidative activity of the compounds was in the following order, Compound 14 > Compound 16 > Compound 15. Compounds 14, 15 and 16 were tentatively identified as 2,4dihydroxycimamic acid, 2,sdihydroxycinnarnic acid and 2,3dihydroxycinnamic acid.